1961
DOI: 10.1139/v61-294
|View full text |Cite
|
Sign up to set email alerts
|

CONFORMATIONAL EQUILIBRIA IN OPEN-CHAIN Α,β-Unsaturated KETONES

Abstract: The infrared and Raman spectra of trans-43-penten-2-one have beer1 ~neasured over the temperature range +30° to -75' and +8j0 to 4-5' respectively. The temperat~~re-dependent changes observed in the spectra indicate that this Icetone exists as an equilibrii~rll mixture of s-cis and s-trans conformational isorners in the liquid state. 'The s-trans forrn is the Inore stable and is present exclusively in the crystalline solid.Silllilar measurements have been carried out on A3-buten-Zone. The infrared and Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…As mentioned above, whether structures such as these two stereoisomers of methyl propenyl ketone actually interconvert depends on conditions including pH, temperature, and solvent, and in general on structural effects such as steric hindrance [ 25 ], conformer energy differences, and barriers to internal rotation [ 26 ]. However, all these effects are way beyond the scope of chemical structure identifiers or a database registration process that should be usable for millions of compounds.…”
Section: Enumeration Of Tautomersmentioning
confidence: 99%
“…As mentioned above, whether structures such as these two stereoisomers of methyl propenyl ketone actually interconvert depends on conditions including pH, temperature, and solvent, and in general on structural effects such as steric hindrance [ 25 ], conformer energy differences, and barriers to internal rotation [ 26 ]. However, all these effects are way beyond the scope of chemical structure identifiers or a database registration process that should be usable for millions of compounds.…”
Section: Enumeration Of Tautomersmentioning
confidence: 99%
“…In nature, there are two conformers of s- cis and s- trans MVKs (molecular sizes: 8.36 Å for s-cis and 7.53 Å for s-trans forms), 7 and their existence ratio depends on the temperature. 2628 In our previous report, it was confirmed that the s-cis form of MVK is the preferred molecular geometry in the 5 12 6 4 cage of MVK + CH 4 sII hydrate in spite of its larger size and that an intracavity conformational change from the s-cis to s-trans form of MVK can be induced by γ-irradiation using an annealing process. 7 The relative energy difference between the two conformers is 0.6 kJ/mol obtained by DFT calculation using the B3LYP model and 6-311++G(d,p) basis set, and the torsional energy barrier from s-cis to s-trans is 6.56 kJ/mol.…”
Section: Resultsmentioning
confidence: 77%
“…It has been studied in the gas phase by microwave spectroscopy [21][22][23][24] and by vibrational spectroscopy in all three phases [25][26][27][28] and also in an argon matrix [29]. There is general agreement that the molecule exists in two conformers, s-trans (2) and s-cis (3) and a potential energy scan around the C2-C3 bond confirms this as shown in Figure 5.…”
Section: -Butene-2-one (Methyl Vinyl Ketone)mentioning
confidence: 68%